The MSH2 c.793-1G>A variant disrupts normal splicing and is associated with Lynch syndrome - Li, Yiming; Yu, Lulu; Cui, Jiajia; Yin, Jiye; Wu, Wei (Frontiers in Oncology, 2023)
Instruction Lynch syndrome (LS) is the most common inherited cancer predisposition disorder of colorectal cancer (CRC) which is associated with pathogenic variants in 4 mismatch repair (MMR) genes. Here, we reported a multi-generation Chinese family clinically diagnosed with LS. Methods To identify the underlying pathogenic gene variants, 30 whole blood samples and 4 colorectal cancer tissue samples and their clinical data were obtained from this four-generation family. Microsatellite instability-high (MSI) testing, immunohistochemistry (IHC), and Whole-Exome Sequencing (WES) were performed to identify the MMR/MSI and the underlying gene variants. The minigene splicing assay and in vitro splicing assay were used to explore the function of this variant. Results MSI-H and dMMR was revealed by the MSI testing and IHC, Whole-Exome Sequencing (WES) in 3 patients successfully identified a splicing variant (c.793-1G>A) in intron 4 of MSH2. Sanger sequencing validated the WES results, and all the “healthy” individuals carrying the variant have been identified in the family by PCR. Bioinformatics analysis and in vitro minigene assay showed that the pathogenic variant affected the splicing process of MSH2 gene to generate 2 kinds defective transcription products, and consequently reduced the expression of MSH2 protein. The mutation carriers were later recommended for colonoscopy and other important cancer diagnostic inspections every 1-2 years because they both have a higher risk of LS. Discussion We found a pathogenic splicing variant (rs863225397, c.793-1G>A) of MSH2 gene, and furtherly confirmed that this mutation plays an important role in LS patients of this pedigree based on the vitro study. Our study indicates that one splicing mutation in the MSH2 gene (c.793-1G>A) causes LS and highlights the importance of LS gene testing.